Advances in Accounting & Auditing Research (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This reprint collection features the complete set of articles from the Special Issue in the Journal of Risk and Financial Management, titled Advances in Accounting and Auditing Research, focusing on timely and emerging themes in various areas of accounting and auditing. The Special Issue is edited by Prof. Dr. Rania Mousa. It is a compilation that provides a comprehensive overview of current research on financial reporting, ESG reporting, earnings management, audit quality, and accounting standards integration. It also presents cutting-edge research which assesses the impact of AI disclosure on financial reporting and performance and the role of technological readiness in enhancing the quality of audit work.